2018
DOI: 10.1177/0265407518780365
|View full text |Cite
|
Sign up to set email alerts
|

The varying roles of parents and the cognitive–emotional variables regarding the different types of adolescent prosocial behavior

Abstract: This article studies the relationship between parental variables (authoritative parental style, maternal and paternal challenges), empathy, and prosocial flow with different types of prosocial behaviors (prosocial behaviors toward different targets and different motivations of prosocial behavior). The sample included 539 students of both sexes (42.5% males; M age ¼ 19.13 years old, SD ¼ 1.92). The hierarchical multiple regression analyses indicated that prosocial behaviors toward family, followed by toward fri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 28 publications
(46 reference statements)
2
10
0
1
Order By: Relevance
“…Specifically, the results indicated that the perspective taking and empathic concerns, cognitive and emotional components of empathy, are related to prosocial behavior toward three different targets: strangers, family and friends. These results are consistent with several previous studies indicating that both aspects of empathy are closely related to the emergence of prosocial behavior (Mesurado, Richaud, Rodriguez, 2018).…”
Section: Relationship Of the Prosocial Behaviors Toward Different Tarsupporting
confidence: 94%
See 4 more Smart Citations
“…Specifically, the results indicated that the perspective taking and empathic concerns, cognitive and emotional components of empathy, are related to prosocial behavior toward three different targets: strangers, family and friends. These results are consistent with several previous studies indicating that both aspects of empathy are closely related to the emergence of prosocial behavior (Mesurado, Richaud, Rodriguez, 2018).…”
Section: Relationship Of the Prosocial Behaviors Toward Different Tarsupporting
confidence: 94%
“…For example, prosocial behavior toward family and toward friends is motivated more by the parental variable than by empathy and positive mental state, while prosocial behavior toward strangers is more motivated by positive mental state and empathy than by the parental variable. Moreover, the same study showed that these three variables (positive mental state, empathy and parental variables), empathy, and prosocial flow explained similar percentages of variance in the different types of the Prosocial Tendency Measure (altruistic, anonymous, responsive, and public) (for more details, see Mesurado, Richaud & Rodriguez, 2018).…”
Section: Relationship Of the Prosocial Behaviors Toward Different Tarmentioning
confidence: 88%
See 3 more Smart Citations